PERANCANGAN VISUAL IDENTITY CENTRAL COFFFEE DI ALAHAN PANJANG - TAUFIK KURNIAWAN, Dr. M. Nasrul Kamal, M.Sn., Riri Trinanda, S.Pd., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
Central coffee is a coffee producer and coffee shop that is located in Alahan Panjang with an owner named Marnofi Hendri. Previously, Central coffee did not yet have an identity, therefore the identity was designed in the form of a logo with color and typography that represented the previous concept so that consumers or prospective consumers could easily remember and increased its brand loyalty.This logo is formed from Mount Talang silhouette that resembles coffee topping, coffee cups and coasters form the letter “C” which is the initial of the object design namely Central Coffee followed by a letter mark beside it to form the word “Central”, and the headline “Coffee” below. This form is in accordance with the concept that Central Coffee used, simple and modern.The analytical method that is used in designing visual Central Coffee is SWOT (Strength,  Weakness, Opportunity, Threat) analysis method to highlight the Central Coffee characteristics. The design of visual identity includes media: manual book, poster, x-banner, name card, sticker, t-shirt, totebag, mug, packaging and backdrop. It is hoped that this visual identity design could help increase brand royalty and get brand awareness so that the design results are right on target, effective and communicative so that it can be known among the wider community.Keywords : Visual Identity, Logo, Central Coffee.